Bornagainism as a Cardinal Teaching of Pentecostalism - Edet, Francis Felix (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
The objective of this study, as its title indicates, is a particular theological grammar: that of being “born again”, a popular concept of Pentecostal Christianity today. Still, it is a subject which despite its immerse theological importance has been largely neglected by mainstream theological scholarship. This is doubtless at least partially because the term “born-again Christianity” has connotations which cause the majority of academia unease: images of dramatic conversion experiences, of a bold religious fervor, of evangelists pleading for listeners to “accept Jesus into their hearts,” and, of course, of certain forms of conservative political activism which on many university campuses subsist only in the shadows. Yet it is not merely religious bias that has contributed to such paucity of interest in Christian new birth: at a more basic level, the phenomenon of being “born again” appears to have its locus in the private confines of the individual subject as a form of immediate presence, which would appear to at least partially shield it from scholarly scrutiny. The concept born-again denotes ‘new birth’ - something consciously experienced, frequently through a memorable conversion and followed by the conviction that one is now a different person, embraced by the presence of a God with whom the born-again Christian has a “personal relationship.” But what can systematic theology possibly say about such a seemingly private religious experience? This is the basic question that leads the researcher to study this topic.